Trihydroxybenzoic acid glucoside as a global skin color modulator and photo-protectant - Chajra H; Redziniak G; Auriol D; Schweikert K; Lefevre F (Dove Medical Press, 2015)
Hanane Chajra,1 Gérard Redziniak,2 Daniel Auriol,3 Kuno Schweikert,1 Fabrice Lefevre1 1Induchem AG, Volkestwil, Switzerland; 2Cosmetic Invention, Antony, 3Libragen SA, Toulouse, France Background: 3,4,5-Trihydroxybenzoic acid glucoside (THBG), a molecule produced by an original biocatalysis-based technology, was assessed in this study with respect to its skin photoprotective capacity and its skin color control property on Asian-type skin at a clinical level and on skin explant culture models. Methods: The double-blinded clinical study was done in comparison to a vehicle by the determination of objective color parameters thanks to recognized quantitative and qualitative analysis tools, including Chroma-Meter, VISIA-CR™, and SIAscope™. Determination of L* (brightness), a* and b* (green–red and blue–yellow chromaticity coordinates), individual typology angle, and C* (chroma) and h* (hue angle) parameters using a Chroma-Meter demonstrated that THBG is able to modify skin color while quantification of ultraviolet (UV) spots by VISIA-CR™ confirmed its photoprotective effect. The mechanism of action of THBG molecule was determined using explant skin culture model coupled to histological analysis (epidermis melanin content staining). Results: We have demonstrated that THBG was able to modulate significantly several critical parameters involved in skin color control such as L* (brightness), a* (redness), individual typology angle (pigmentation), and hue angle (yellowness in this study), whereas no modification occurs on b* and C* parameters. We have demonstrated using histological staining that THBG decrease epidermis melanin content under unirradiated and irradiated condition. We also confirmed that THBG molecule is not a sunscreen agent. Conclusion: This study demonstrated that THBG controls skin tone via the inhibition of melanin synthesis as well as the modulation of skin brightness, yellowness, and redness. Keywords: skin color, UV spots, pigmentation, sun damage, melanin